Hardy’s and Miyachi’s theorems for the first Hankel – Clifford transform - El, Kassimi M.; Fahlaoui, S. (Ukrains’kyi Matematychnyi Zhurnal, 2019)
UDC 517.5 We present an analog of Hardy’s and Miyachi’s theorems for the first Hankel – ,Clifford transform.